Aborto provocado e sua interface com a gravidez não planejada - Costa, Carolina Barbosa Jovino de Souza (2012)
This is a research study with quantitative and transversal approach aiming to investigate the induction of abortion and its relationship with an unplanned pregnancy, in comparison with natural abortion. It also aimed to analyse the demographic, socioeconomic and reproductive aspects of both methods of abortion; verify the knowledge and use of contraceptive methods prior to the interrupted pregnancy through induced and natural abortion and know which methods are used for induced abortion and it motifs. The study took place at the District Hospital Gonzaga Mota in Barra do Ceará and General Hospital Dr. Cesar Cals (HGCC), from June until December of 2011. The population consisted of women in abortion and over 18 years of age who were being assisted at the hospitals during data collection. The interview followed a structured questionnaire that was previously tested. The study consisted in the end with 70 participants, being 33 (47,1%) women who induced abortion and 37 (52,9%) with natural abortion. The data were analysed with descriptive statistics and the comparison of the means of these variables and the type of abortion were done with the Student t test for independent data and with unequal variance (analysed with Levene’s test). It was compared only for induced abortion, the percentage of dichotomous variables with the z test for proportions. The association analysis between the type of abortion and the nominal variables were conducted with 2 and likelihood ratio. It was calculated the chance ratios (CR) with its respective IC95% between the type of abortion and these variables. It was considered as statistically significant, analysis with p<0,05. Amongst the demographic and socioeconomic variables, only the average number of people in the family presented association with the type of abortion (p= 0,042). Regarding reproductive variables and marital status, there was an association between planning of a pregnancy and abortion (p<0,001) (RC=2,4; IC95%: 1,7-3,3). This shows that an unplanned pregnancy was a risk factor for induced abortion. The average time of union with their partner was higher in women with natural abortion than in those with induced abortion (p= 0,041). It was shown that the male participation in the decision of an abortion is a risk factor for induced abortion (p= 0,002). Variables regarding information and access to contraceptive methods prior to the abortion were not significant to the type of abortion. There was an association between the use of AOC and type of abortion, being the use of AOC a protective factor to induced abortion (p= 0,040). The belief that a pregnancy would not occur with themselves was significant with the type of abortion (p= 0,003). Herbal teas and misoprostol were the most frequent methods mentioned by the women to induce an abortion, being their low economical situation, followed by an unstable relationship and unpreparedness to take care of a child the main reasons to render towards these methods. It was concluded that promoting effective methods of family planning, prioritizing poorer populations, with strategies that assures male participation represent means to reduce induced abortions.